Ethnicity and the American short story - Brown, Julie, 1961- (Garland reference library of the humanities ;, 1997)
How do different ethnic groups approach the short story form? Do different groups develop culture-related themes? Do oral traditions within a particular culture shape the way in which written stories are told? Why does ""the community"" loom so large in ethnic stories? How do such traditional forms as African American slave narratives or the Chinese talk-story shape the modern short story? Which writers of color should be added to the canon? Why have some minority writers been ignored for such a long time? How does a person of color write for white publishers, editors, and readers?Each